Measurement Equivalence of E‐Scale and In‐Person Clinic Weights. Issue 7 (5th June 2019) - Pebley, Kinsey; Klesges, Robert C.; Talcott, G. Wayne; Kocak, Mehmet; Krukowski, Rebecca A.
Abstract : Objective: The current study aimed to determine whether electronic scale (e‐scale) weight measurements are concordant with in‐person clinic weights. Methods: E‐scale and in‐person clinic weight measurements from 248 active duty military personnel enrolled in a weight‐loss intervention study were used. E‐scale and clinic measurements were matched and tested to determine whether measurements were significantly different from each other. Equivalence between the two measurements was tested among the cohort and when stratifying by gender, BMI, race, and age. The study also examined whether matching the times of clinic and e‐scale measurements or averaging multiple measurements was optimal, and whether using e‐scale and clinic measurements from the same day or across a specified amount of time was acceptable. Results: Overall, e‐scale and clinic measurements were significantly different from each other but did not differ from equality. Additionally, using e‐scale and clinic weight measurements that were taken on the same day may be a preferable method compared with using measurements within a week of each other, which leads to weight underprediction among e‐scale measurements. Conclusions: E‐scales display good measurement concordance. E‐scales may be helpful when studying highly mobile populations, such as military personnel, and could potentially eliminate the need for in‐person visits.